2020
DOI: 10.3390/cancers12082132
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Sequential Systemic Therapies for Advanced Hepatocellular Carcinoma: A Decision Analysis

Abstract: Background: An optimal sequential systemic therapy for advanced hepatocellular carcinoma (HCC) has not been discovered. We developed a decision model based on available clinical trials to identify an optimal risk/benefit strategy for sequences of novel systemic agents. Methods: A Markov model was built to simulate overall survival (OS) among patients with advanced HCC. Three first-line (single-agent Sorafenib or Lenvatinib, and combination of Atezolizumab plus Bevacizumab) followed by five second-line treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 40 publications
(92 reference statements)
0
17
1
Order By: Relevance
“…The current study compared the e cacy of nivolumab and regorafenib, the most frequently used ICI and TKI, for HCC patients with advanced stages who failed sorafenib. In a mathematical Markov model reported by Cabibbo et al that simulated treatment effect of sequential systemic therapies among patients with advanced HCC based on data of clinical trials, the simulated estimates of median OS were signi cantly higher for sofafenib followed by nivolumab compared to sorafenib followed by regorafenib (27 months vs 18 months) [22]. In the current study, we found that using nivolumab had a trend of better ORR and DCR than using regorafenib, but there was no statistical difference.…”
Section: Discussioncontrasting
confidence: 43%
“…The current study compared the e cacy of nivolumab and regorafenib, the most frequently used ICI and TKI, for HCC patients with advanced stages who failed sorafenib. In a mathematical Markov model reported by Cabibbo et al that simulated treatment effect of sequential systemic therapies among patients with advanced HCC based on data of clinical trials, the simulated estimates of median OS were signi cantly higher for sofafenib followed by nivolumab compared to sorafenib followed by regorafenib (27 months vs 18 months) [22]. In the current study, we found that using nivolumab had a trend of better ORR and DCR than using regorafenib, but there was no statistical difference.…”
Section: Discussioncontrasting
confidence: 43%
“…PFS is a composite endpoint not influenced by post-progression survival and that avoids crossover treatment bias. Modeling sequential treatments, PFS represents the primary endpoint for first-line therapy in ICI trials, as demonstrated by a recently published decision model [ 40 ]. Although efforts have been made to improve the surrogacy between PFS and OS in immunotherapy trials—by modifying the threshold percentage to define PFS or the response criteria with Immune Response Evaluation Criteria in Solid Tumors (iRECIST)—PFS surrogacy for OS remains weak both at trial and individual level [ 10 , 11 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the window of intervention before reaching the irreversibility time-point for BCLC-C and D patients is extremely small but should be considered during clinical decision making. This is particularly relevant now since there are several systemic therapeutic options available [46].…”
Section: In Both Scenarios We Propose Prioritising Symptomatic Treatmentioning
confidence: 99%